Understanding the Interaction of glycine amino acid with graphene: An Alternative Theoretical Approach Based on Density Functional Theory - maedeh kamel; kamal Mohammadifard (Journal of Chemistry Letters)
The present work utilizes density functional theory (DFT) calculations to investigate the interaction of glycine amino acid with graphene. Quantum chemical calculations by DFT provide detailed geometrical parameters, electronic properties and the adsorption energies for the graphene and three different amino acid configurations on the graphene. DFT calculations confirmed the energetic stability of the optimized geometries and revealed that amino acid molecule adsorbed on the graphene through weak van der Waals (vdW) interaction, which means that the adsorption is physisorption process. The results of the theoretical investigations show that the adsorption of the amino acid molecule on the graphene surface results in a decrease the chemical potential (µ). Thus, the reactivity and electrical conductivity increase upon the adsorption process.